2004
DOI: 10.1088/0268-1242/20/2/003
|View full text |Cite
|
Sign up to set email alerts
|

On the properties of indium doped ZnO thin films

Abstract: Thin films of undoped and In-doped zinc oxide, prepared using chemical spray pyrolysis, were investigated using x-ray diffraction, optical transmission and absorption spectra, SEM, resistivity measurements, x-ray photoelectron spectroscopy and photoluminescence studies. A doping level of 1 at% indium was found to give lowest resistive films and enhanced optical transmission. But increasing the doping percentage resulted in lower optical transmission. XPS investigations revealed the presence of elemental chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(64 citation statements)
references
References 35 publications
7
54
1
2
Order By: Relevance
“…It can be seen that the grain size of the films decreases by increasing indium incorporation. This behavior of the www.pss-c.com grain size increasing the doping level is in agreement with those reported for ZnO thin films prepared by the same process [7,9]. This effect can be explained if it is considered that (i) indium atoms do not substitute zinc ions, instead they occupy interstitial sites resulting in a large number of dislocations and (ii) probable formation of compound which is growing along with ZnO:In.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…It can be seen that the grain size of the films decreases by increasing indium incorporation. This behavior of the www.pss-c.com grain size increasing the doping level is in agreement with those reported for ZnO thin films prepared by the same process [7,9]. This effect can be explained if it is considered that (i) indium atoms do not substitute zinc ions, instead they occupy interstitial sites resulting in a large number of dislocations and (ii) probable formation of compound which is growing along with ZnO:In.…”
supporting
confidence: 88%
“…Indium incorporation in to the compounds caused reorientation which exhibited itself as (101) preferred orientation, whereas (002) peak intensities observed to be decreased. The crystal structure of the obtained films is better than those reported for the films deposited at 400 and 450 o C substrate temperatures by the same method [7,8]. Because, the properties of the film depend on the experimental parameters such as spray solution molarity, spray rate, substrate temperature, carrier gas and droplet size.…”
mentioning
confidence: 67%
“…The CaF 2 capping layer did not prevent the degradation of the film but delayed it by up to two weeks. The interference fringe pattern in the transmission spectrum indicates that the film surface was highly reflecting and there was not much scattering or absorption loss in the film [9].…”
Section: Resultsmentioning
confidence: 99%
“…Figure We have previously reported that doping of CuCl by co-evaporation with ZnCl 2 results in the quenching of the excitonic emission one day after deposition measured by UV-VIS spectroscopy and is accompanied by a decrease in the transmittance of the Zn-doped films [6]. For optoelectronic device applications both the electrical conductivity and the optical transmission should be as high as possible [9]. Therefore it is important to ensure that the transmissivity is not compromised by doping.…”
Section: Resultsmentioning
confidence: 99%
“…More massive Group III elements, such as indium [21], [22], gallium [23], aluminum (Al) [24], and boron (B), are known n-type dopants in ZnO [25]. They have been incorporated in ZnO mostly to form transparent-conducting electrodes for solar cells [26] or lightemitting diodes [26], [27].…”
Section: Introductionmentioning
confidence: 99%